Trinitas dan Tri Murti : Tinjauan Religionum terhadap Trinitas Kristen dan Trimurti Hindu Serta Implikasinya bagi Kerukunan Umat Beragama - Agus Parasian Sinaga; Demosari Fabriensy Nainggolan (Lumen: Jurnal Pendidikan Agama Katekese dan Pastoral, 2024)
Religious conflicts in Indonesia still occur to this day even though Indonesia is known as a plural country. There are still claims that the teachings of one religion are better than other religions. In this study, the author discusses the concept of the Trinity in Christianity and Trimurti in Hinduism, and the implications of both concepts for inter-religious harmony. The Trinity, consisting of the Father, Son, and Holy Spirit, is the core of Christianity that emphasises unity and diversity in one God. The Trimurti consisting of Brahma (Creator), Vishnu (Sustainer), and Shiva (Destroyer) describes different aspects of God in Hinduism. Analyses were conducted using a religio-cultural approach to understand how these two concepts can complement or contradict each other. The research shows that although there are fundamental differences in the understanding of divinity between Christianity and Hinduism, there are also common points that can be used as a basis for interfaith dialogue. This research provides theological insights and practical solutions to create social harmony.